Oxidation of Iodine to Dihaloiodate(I) Salts of Amines With Hydrogen Peroxides and Their Crystal Structures - Prinčič, Griša Grigorij; Maselj, Nik; Goreshnik, Evgeny; Iskra, Jernej (Frontiers in Chemistry, 2022)
Herein we report a general preparation of dihaloiodate salts of heterocyclic amines (tertiary and quaternary) with sterically accessible and hindered nitrogen atom. A number of such compounds were prepared from preformed HICl2 or HIBr2 formed in situ by the reaction of corresponding hydrogen halide, iodine and H2O2. The salts of 1,4-diazabicyclo[2.2.2]octane (DABCO) and its methylated derivatives, 1,3,5,7-tetraazaadamantane (HMTA), diazabicycloundecene (DBU) and 2,4,6-tri-tert-butylpyridine (TBP) were obtained in excellent yields and their structure was determined by NMR and Raman spectroscopy and single crystal X-ray diffraction. Non-hindered bases such as DABCO, HMTA and DBU formed IX2− salts, which further decomposed to complexes with interhalogen compounds due to formation of N…X halogen bonds. The dihaloiodiate(I) salts of sterically hindered 2,4,6-tri-tert-butylpyridine were stable. Its dichlorobromate(I) salt was also prepared via a different synthetic method using N-chlorosuccinimide as oxidant.